The Meaning of The Shen Nong Da Di's (神农大帝Shen Nong Da Di) Birthday Ceremony at Ngo Kok Ong Temple Cibarusah, West Java - Dhyana Widya; C. Dewi Hartati (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
This article discusses the meaning of the tradition Shen Nong Da di’s birthday ceremony (sejit) at Ngo Kok Ong Temple, Cibarusah, West Java. Ngo Kok Ong temple put Shennong Dadi in Hokkien dialect is called Sin Long Tay Te which means Agricultural Emperor as the main deity. The research methodology and data collection techniques used are qualitative methods. Data collection by indepth interviews and participant observations. Observations and participant observation carried out during the ceremony of Shen Nong's birthday from 26 June 2019 to 29 June 2019 with a descriptive analysis design. The purpose of this research is to describe the meaning of traditions at the Shen Nong’s birthday ceremony. The results of the research show that there are various traditions during this ceremony, prayer together, mediumship such as making amulet, slashing the tongue, stamping on coals lion dance and liong performances, and the tradition of electing locu. These various traditions have religious functions, social functions and psychological functions. Apart from that, the contained meaning in this tradition is the symbolic meaning and philosophical meaning for every Chinese community.